2021
DOI: 10.3390/rs13142775
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of CWSI-Based Plant Water Stress Estimation with Diurnal Acquisition Times in a Nectarine Orchard

Abstract: Unmanned aerial vehicle (UAV) remote sensing has become a readily usable tool for agricultural water management with high temporal and spatial resolutions. UAV-borne thermography can monitor crop water status near real-time, which enables precise irrigation scheduling based on an accurate decision-making strategy. The crop water stress index (CWSI) is a widely adopted indicator of plant water stress for irrigation management practices; however, dependence of its efficacy on data acquisition time during the day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Midday stem water potential and stomatal conductance have been traditionally used to assess tree water status due to their robust and fast response to soil water limitations ( Naor 2000 ; Van Beek et al., 2013 ; Conesa et al., 2019 ). Many studies have reported strong relationships between thermal-based indices, stem water potential and stomatal conductance ( García-Tejero et al., 2018 ; Ahumada-Orellana et al., 2019 ; Park et al., 2021 ). Our results are aligned with those studies and show high correlation coefficients between thermal-based indices and traditional water status indicators ( Figure 8B ).…”
Section: Discussionmentioning
confidence: 99%
“…Midday stem water potential and stomatal conductance have been traditionally used to assess tree water status due to their robust and fast response to soil water limitations ( Naor 2000 ; Van Beek et al., 2013 ; Conesa et al., 2019 ). Many studies have reported strong relationships between thermal-based indices, stem water potential and stomatal conductance ( García-Tejero et al., 2018 ; Ahumada-Orellana et al., 2019 ; Park et al., 2021 ). Our results are aligned with those studies and show high correlation coefficients between thermal-based indices and traditional water status indicators ( Figure 8B ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the accuracy of the midday system in assessing CWSI values, as hypothesized by past researchers, additional research is required to determine the optimal time of day for this estimation (Santesteban et al, 2017). However, only a few efforts have been made to study CWSI diurnal variations (e.g., Park et al, 2021), particularly with TIR data collected in the morning utilizing UAS. Some studies showed that the TIR image processing failed due to surface temperatures' poor contrast, causing TIR image processing issues due to missing images from the thermal sensor (Martínez et al, 2017;Santesteban et al, 2017;Zhang et al, 2019).…”
Section: Ns Wetmentioning
confidence: 99%
“…It was shown in previous studies that several crop-based indices such as canopy temperature [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], chlorophyll content [ 20 , 21 , 22 ], and vegetation indices [ 23 , 24 , 25 , 26 , 27 , 28 ], can be used to determine crop water content, and have been employed for managing water in irrigated agriculture [ 29 , 30 , 31 , 32 , 33 ]. Canopy temperature [ 34 ] thermal indices obtained with ground-based or aerial-based sensors, can indicate crop transpiration and water stress, allowing the development of indices that assess vine water status [ 13 , 35 ] in a non-destructive and non-invasive way [ 18 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CWSI method has been widely used in irrigated crops, and is considered a standard method. Many studies have been carried out in different crops, including nectarines [ 17 , 19 ], soybean [ 48 ], cotton [ 49 ], tomato [ 50 ], olive trees [ 51 ] and vines [ 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%